Speed Control Strategy for Dynamic Property Under the Condition of Small Attachment Coefficient of HEV with Electric-mechanical Control CVT - Ye Ming; Ma Xiang; Peng Jiang; Li Si (Jixie chuandong)
According to the performance requirements under the condition of small attachment coefficient,the speed control strategy is built in the hybrid electric vehicle equipped with electric- mechanical continuously variable transmission. In the start- up phase of vehicle,the start- up mode can be determined by analyzing the battery state of charge（ SOC）. Under the working condition of speed up climbing and in different start- up modes,the CVT ratio control under the condition of small attachment coefficient can be decided through the demand torque,and by this CVT ratio control to insure the vehicle driving wheel without slipping phenomenon under the condition of the accelerator fully open. The speed control strategy is built in MATLAB / Simulink /Stateflow and simulated in CRUISE which vehicle model is built. The simulation results shows that torque of driving cycles gets a reasonable distribution with this shifting strategy,and vehicle dynamic property promotion is gotten.